Educational Management in a Changing World at the Faculty of Architecture and Planning Thammasat University - Verapreyagura, Pornphan (วารสารการบริหารและนิเทศการศึกษา, 2024)
Education reforms in a changing world arose first against neo-classical education or 'humanistic education.' Its effects forced instructors to teach for testing, changed curriculum standards, and students became academic entrepreneurs. The Faculty of Architecture and Planning at Thammasat University adjusted to these changes. This quantitative research approach focuses on educational management guidelines. The open-ended questionnaire and structural interview are its main instruments. Percentage, mean, mode, standard devia- tion, F-test, and Pearson Correlation were used for analyzing the data. The research finding reveals that the mainstream and the alternative aspects in the educational management guidelines concern with external factors such as the entrepreneurs' satisfaction, standardiza- tion, and the students' voices. The entrepreneurs' satisfaction relates to general qualifications, identifications, and abilities of the graduates selecting between government university and private university at a rate of 3:1. Standardization means new curriculum structure; 25% of general basic courses, 10-15% of elective courses, and 60-65% of architectural program courses. The students' voices indicate a desire to reduce central control and standardized testing.